The response of transgenic strawberry plants overexpressing a drought induced gene to water stress (Journal of Applied Botany and Food Quality, 2013)
Transgenic strawberry plants expressing a chitinase gene were evaluated for their performance during water stress. Transgenic and non-transgenic plants were assigned to three different soil water contents (SWC). They were kept under well-watered, moderately watered or stressed water conditions. At fi nal stage of experiment, dry matter components, leaf area, photosynthesis rate, water-use effi ciency (WUE) and water use per leaf area (WULA) were measured. Transgenic lines showed vigorous growth as compared with non-transgenic plants. Leaf area (LA), leaf dry matter (LDM), root dry matter (RDM) and total dry matter (TDM) of well-watered and water-stressed plants of transgenic lines were signifi cantly higher than those of non-transgenic plants. The WUE increased signifi cantly in transgenic lines, while water use (WU) per leaf area reduced in transgenic plants relative to control plants. Photosynthetic rates were not different between transgenic and non-transgenic plants. Soil water contents signifi cantly affected dry matter production, and photosynthetic rates. Transgenic plants also showed vigorous growth in comparison to non-transgenic plants when grown in vitro. Shoot, root and total fresh and dry weight of in vitro transgenic lines were significantly higher than those of nontransgenic plants.